A tecnologia na sala de aula: alternativa para o ensino de botânica no ensino médio - Oliveira, Evandro Brandão de (2020)
Plants are important in the characterization of biomes and are present in our daily lives, being essential to the maintenance of life on the planet, and their study is used in the most different areas of human knowledge. Bringing the student to understand a study of the study of botany can generate an advance in the understanding and importance of plants in the environmental, educational and social context and, thus, promote the teaching of botany. Looking at textbooks with a traditional approach, a difficulty in teaching and learning botany in high school, there is no excessive use of memorizing concepts related to the subject. This way of using is unattractive and distant from the world in which our young people live, the digital world. The objective was to develop an educational game on the Game with students platform, encourage the use of new methodologies that facilitate the teaching and understanding of Botany in high school, promote the role of students, investigative teaching and verify the potential of the digital game for use in the classroom by biology students. The target audience chosen to participate in the research was composed of students from the 2nd Grade of Public School located in the city of João Pessoa-PB. 134 students participated in the research, divided into two groups, one called experimental with 66 students who use the didactic game and a control group with 68 students who do not use the didactic game. The research adopted in this work had a qualitative and quantitative approach and followed the participant research method. In order to carry out this research, we based on the botanical content that would be taught to students throughout the year. To obtain data, questionnaires of the type were applied: polling, pre-test, post-test and game evaluation. The analysis of the data obtained with the questionnaires revealed what the literature has already shown, little interest by students in botany when the subject was approached in a traditional way and better teaching, learning and interest in the use of the subject's gamification with the use of digital technology . In the pre-test and post-test questionnaires, there was an improvement in the learning of students in the experimental group. The students' satisfaction with the use of educational games in the classroom was confirmed with the data obtained in the game evaluation questionnaire. The main product generated in this work was the production of a didactic game called The Botany Game of the Plataform Game type that was used by the students of the experimental group, promoting playfulness, the protagonism of students and teaching by investigation. It is concluded, therefore, that the didactic game The Botany Game improved the learning of the students of the experimental group and that this type of alternative digital methodology is efficient in promoting the teaching of botany.